Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Average daily weight gain of Iberian fattening pigs when grazing natural resources - Rodríguez-Estévez, Vicente; Sánchez-Rodríguez, Manuel; García, Antón R.; Gómez-Castro, a Gustavo (Livestock Science, 2011)
In spite of the growing interest in organic farming and sustainable production, there is a lack of information about the performance of pigs when they feed only on natural resources. This research studied the fattening pattern during the montanera (free-range grazing on acorns and grass during autumn and winter, without any supplementary feed or mineral complement) of the Iberian pig in the dehesa (Quercus ilex open woodlands) in order to know the average daily gain (ADG) and to analyze the inﬂuence of three factors: year of montanera, age and sex of pigs. The fattening data were obtained from two ﬂocks of castrated pigs during the ﬁrst two months (from November the ﬁrst) of two consecutive montaneras (2003 and 2004) on the same farm. Pigs (from 111.8± 0.9 kg BW at introduction) were individually weighed every 15 days in the early morning, with no food intake since the previous evening. The ADG for all pigs was 0.76± 0.01 kg/day; however, some variations were observed according to the year (0.74±0.02 kg/day in 2003 vs. 0.78±0.02 kg/day in 2004; pb0.05), the sex (0.78±0.02 kg/day for males vs. 0.72± 0.02 kg/day for females; pb0.01) and the age (0.71±0.02 kg/day for pigs younger than a year vs. 0.83±0.02 kg/day for pigs older than a year; pb0.001); however a factorial 3-way ANOVA does not show signiﬁcant interaction between factors. Comparing the fortnights periods, the lowest ADG was measured in the ﬁrst 15 days of montanera (0.60±0.02 kg/day), and the highest ADG occurred in the second one (0.85±0.02 kg/day). Later on, the datasets were adjusted with the GLM procedure for the fixed effects of the year of the montanera, the age and the sex. With the adjusted datasets, different regression models for the fattening in montanera were established; the best adjusted of those was the potential model (Y= 0.32*X 1.22 ; X= days of montanera; and Y= kg life weight gained during the montanera). According with this model pigs would need an average of 58 d to fatten 46 kg, as the Iberian Breed Quality Standards demand. Finally, the results show that the age and sex, as factors that inﬂuence the ADG, should be taken into close account to choose pigs and that it is possible to reach a high ADG grazing only with natural resources, following appropriate management strategies such as rationing in order to obtain the beneﬁts of compensatory growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: acorn; Compensatory growth; Extensive farming; Free ranging; Grass; Organic farming; Sustainable production